ANALYSIS OF FISH DELIVERY IN PANDEGLANG BANTEN: A CASE STUDY OF LABUAN FISH AUCTIONS - Agung Prayudha Hidayat; Laily Rochmatul Charky; Sesar Husen Santosa (Center for Study and Journal Management FTI UMI, 2022)
Fishery commodities are one of the categories of goods that are easily damaged so that quality is maintained as a key factor in shipping goods. This research analyze on the scheme of determining the mode of transportation using Break Even Point (BEP) and analyzing the optimization of the route by minimizing the distance traveled by using the Traveling Salesman Problem (TSP) method. The results of this research is optimizing the mode of transportation using private modes with the number of trips under 576 trips and the optimal route of travel that is Pandeglang-Jakarta-Bogor-Pelabuhan Ratu-Pandeglang of 408 Km.